Wm. E. Miller et al., Charter and Laws of Iowa City 13 (1857) - (:unkn) unknown (My University, 1853)
Ordinance no. 6-An Ordinance to Prevent Shooting, §§ 1-2. Passed April 25, 1853; Published April 27, 1853: Prohibited shooting any gun or firearm within the corporate limits of Iowa City. Violators fined not less than one nor more than ten dollars.
Keywords: DISCHARGE